2011
DOI: 10.1093/icb/icr095
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian Immune Defenses against Chytridiomycosis: Impacts of Changing Environments

Abstract: Eco-immunology is the field of study that attempts to understand the functions of the immune system in the context of the host's environment. Amphibians are currently suffering devastating declines and extinctions in nearly all parts of the world due to the emerging infectious disease chytridiomycosis caused by the chytrid fungus, Batrachochytrium dendrobatidis. Because chytridiomycosis is a skin infection and remains confined to the skin, immune defenses of the skin are critical for survival. Skin defenses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(184 citation statements)
references
References 88 publications
2
176
1
5
Order By: Relevance
“…Microbial invasion and infection due to disruptions of the surface cell layer occur frequently (25). To our knowledge, βγ-CAT is the first example of a naturally existing complex of bacterial PFT-like protein and TFF in vertebrates (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial invasion and infection due to disruptions of the surface cell layer occur frequently (25). To our knowledge, βγ-CAT is the first example of a naturally existing complex of bacterial PFT-like protein and TFF in vertebrates (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune responses, such as secretion of antimicrobial peptides, are one of several factors known to influence amphibian susceptibility (Rollins-Smith et al 2011); other factors include symbiotic skin bacteria that inhibit Bd (Harris et al 2006), microhabitat preferences (Brem andLips 2008), and thermoregulatory behavior (Richards-Zawacki 2010). The adaptive immune response of X. laevis appears to be inhibited by Bd (RollinsSmith et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The common laboratory species Xenopus laevis, which appears to be tolerant of Bd infection, does produce Bd-binding antibodies in response to repeated Bd exposure (Ramsey et al 2010), but the susceptible species Rana muscosa, R. sierrae, and Silurana tropicalis, do not demonstrate a robust immune response with Bd infection Rosenblum et al 2012). It has been demonstrated that Bd may produce factors that reduce or evade the normal cellmediated immune response Rollins-Smith et al 2011), and recently Bd zoospores and supernatant were found to inhibit splenic lymphocyte functioning and proliferation, and increase apoptosis in vitro (Fites et al 2013). However, certain amphibian species can acquire resistance in the form of reduced infection burden and mortality after repeated exposures to the pathogen (McMahon et al 2014).…”
Section: Facets Of the Amphibian Immune Systemmentioning
confidence: 99%